2021
DOI: 10.1111/jgh.15519
|View full text |Cite
|
Sign up to set email alerts
|

Propensity score‐matched analysis of endoscopic resection for recurrent colorectal neoplasms: A pilot study

Abstract: Background and Aim Local residual/recurrent colorectal lesions after endoscopic resection (ER) are difficult to treat with conventional ER. Underwater endoscopic mucosal resection (UEMR) and endoscopic submucosal dissection (ESD) are reportedly effective. We investigated the appropriate indications of ESD and UEMR for recurrent colorectal lesions. Methods This single‐center, retrospective, observational study was conducted at a tertiary cancer institute. Patients who underwent UEMR or ESD for residual/recurren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…Only two retrospective studies investigated the efficacy of UEMR for recurrent lesions after endoscopic resection. 31 , 32 One retrospective analysis compared 36 UEMR and 44 CEMR procedures. 32 It showed that UEMR had significantly better EBR (47% vs. 16%) and endoscopic CRR (89% vs. 32%) than CEMR.…”
Section: Outcomes Of Uemr For Recurrent Lesions After Endoscopic Rese...mentioning
confidence: 99%
See 2 more Smart Citations
“…Only two retrospective studies investigated the efficacy of UEMR for recurrent lesions after endoscopic resection. 31 , 32 One retrospective analysis compared 36 UEMR and 44 CEMR procedures. 32 It showed that UEMR had significantly better EBR (47% vs. 16%) and endoscopic CRR (89% vs. 32%) than CEMR.…”
Section: Outcomes Of Uemr For Recurrent Lesions After Endoscopic Rese...mentioning
confidence: 99%
“…Table 4 shows literature reports assessed for the efficacy of underwater endoscopic mucosal resection for recurrent colorectal polyps. Only two retrospective studies investigated the efficacy of UEMR for recurrent lesions after endoscopic resection 31,32 . One retrospective analysis compared 36 UEMR and 44 CEMR procedures 32 .…”
Section: Outcomes Of Uemr For Recurrent Lesions After Endoscopic Rese...mentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have demonstrated the safety and efficacy of UEMR for colorectal lesions. [2][3][4][5][6][7][8][9][10] We performed a prospective randomized controlled trial (RCT) of UEMR and CEMR for 10-to 20-mm sessile colorectal lesions and reported that UEMR achieved a significantly better R0 resection rate than CEMR, without increasing the adverse events or procedure time. 11 Thus, UEMR is expected to become a standard procedure for removing colorectal polyps with a diameter of 10-20 mm.…”
Section: Introductionmentioning
confidence: 99%
“…as an alternative to CEMR for removing large, flat colorectal neoplasms. Several studies have demonstrated the safety and efficacy of UEMR for colorectal lesions 2–10 . We performed a prospective randomized controlled trial (RCT) of UEMR and CEMR for 10‐ to 20‐mm sessile colorectal lesions and reported that UEMR achieved a significantly better R0 resection rate than CEMR, without increasing the adverse events or procedure time 11 .…”
Section: Introductionmentioning
confidence: 99%